Frequency of Meningitis Among Infants and Young Children With Clinically Diagnosed First Time Febrile Seizure - Mahamuduzzaman, Abu Shoyeb Md; Banu, Nazneen Akhter; Anowar, Asma Bint; Hossain, Mohammad Delwar; Karim, Farhana; Qyuoom, Md Abdul; Saleha, Rawshon (Sir Salimullah Medical College Journal, 2022)
Background: Patients with bacterial meningitis (BM) frequently present with febrile seizures (FS) without any signs or symptoms of BM. To perform a lumbar puncture on all FS patients to rule out meningitis is still debatable. The goal of this study was to estimate the frequency of meningitis among first-time febrile seizures (FTFS). Methods: From July 2013 to June 2014, a cross-sectional study was conducted at Sir Salimullah Medical College and Mitford Hospital, Dhaka. CSF and blood reports and detailed histories and examinations were examined in children aged 6 months to 36 months with FTFS (simple or complex). Results: The first complex febrile seizure (FCFS) and the first simple febrile seizure (FSFS) occurred in 58% and 42% of the 73 children included in this study. 11 (15%) cases had meningitis based on CSF and blood reports, where 2 (3%) had confirmed BM, 2 (3%) had probable BM, and 7 (10%) had viral meningitis (PVM). One of two children with confirmed BM had Klebsiella spp. in CSF culture and Streptococcus pneumoniae in CSF gram stain. Others with probable BM had CSF pleocytosis with low sugar and high protein levels. Leukocytosis was found in all four children with BM. Two of the seven children with PVM had isolated pleocytosis, one had low sugar, and four had high protein CSF. Blood cultures were negative in all 11 meningitis cases. Conclusion: Although meningitis is common in FCFS, this study found no cases of BM children with FSFS, though PVM was not uncommon. Sir Salimullah Med Coll J 2022; 30: 108-114